Knowledge, Perception and Attitude Regarding Generic Medicines among Iraqi Physicians - Ali Azeez Al-Jumaili; Layla Abdullah Mahdi; Dheyaa Jabbar Kadhim (University of Minnesota Libraries Publishing, 2020)
Objectives: The study aim was to explore the knowledge, perceptions, and attitudes of Iraqi physicians regarding generic and locally manufactured medicines. Methods: A total of 124 physicians were involved in this cross -sectional study. The convenience sample was collected from five public hospitals in Baghdad. A self-administered questionnaire was distributed and collected in-person. Fisher's Exact Test was used to measure the association between physician years of experience, gender and categorical (perception and knowledge) variables. Results: Most respondent answers regarding the knowledge of generic medicines were incorrect. Only up to one-third of the participants knew that generic medicines are therapeutically equivalent to brand name medicines (26.6%), as safe as brand name medicines (34.7%) and required to meet similar safety standards as brand name medicines (12.1%). With respect to perception, many physicians had negative perceptions about generic medicines such as viewing generic medicines as lower quality (57.3%) and cause more side effects (41.1%) compared to brand name medicines. Regarding physician attitudes toward generic medicines, about two-thirds (64.5%) of the physicians were willing to prescribe low cost medicines; however, only about half (51.6%) of the physicians reported they offer generic medicines to their patients. Finally, 64.5% of the participants were not comfortable with pharmacist replacing prescribed brand with generic medicines. Conclusions: In general, Iraqi physicians have negative perceptions and attitudes about generic and locally manufactured medicines. Significant gaps were identified in the knowledge and perceptions among physicians regarding generic medicines especially in relation to efficacy and safety of generic medicines.   Article Type: Original Research